Reactivity of the O2+.(H2O)n and NO+.(H2O)n cluster ions in the D-region of the ionosphere - Sharma, Sainish (2018)
The structure, spectroscopy and reactivity of hydrated dioxygenyl cluster ions O2+.(H2O)n with n = 1 – 5 has been theoretically investigated for the first time to understand potential reaction pathways that may convert O2+, present in high abundance in the upper layers of the ionosphere (E-region), into protonated water clusters, which are the predominant positively charged ion species in the lower D-region. The reactivity of hydrated nitrosonium as NO+.(H2O)n with n = 4 – 5 has also been reinvestigated to clarify the potential intramolecular reaction for the formation of nitrous acid and a protonated water cluster. Lowest energy geometries, binding energies and harmonic vibrational frequencies have been obtained for O2+.(H2O)n (n = 1 – 5) cluster ions. Through performing geometry optimisation calculations on O2+.(H2O) using coupled cluster theory (CCSD(T)), second order Møller-Plesset perturbation theory (MP2) and density functional theory (DFT) with a wide range of exchange-correlation functionals, it was found that the MP2/6-311++G** level of theory was reliable for the calculation of minimum energy geometries and harmonic vibrational frequencies. In particular, methods that include 100% exact Hartree-Fock exchange such as MP2 and M06-HF were found to accurately describe the charge distribution in the clusters. MP2-based Born-Oppenheimer ab initio molecular dynamics (AIMD) simulations of the reactions of the O2+.(H2O)n and NO+.(H2O)n cluster ions to form protonated water clusters reveal different mechanisms for the O2+ and NO+ based ions. AIMD simulations of O2+.(H2O)n (n = 2 – 5) with initial velocities of the atoms sampled from the Maxwell-Boltzmann distribution at 220 K show that following charge transfer, a reaction to form a protonated water cluster and OH radical occurs rapidly where the neutral O2 molecule is just a spectator. In contrast, the reaction of NO+.(H2O)n (n = 4 – 5) has been hypothesised to involve an intracluster reaction, but no reaction is observed in the AIMD simulations using thermal initial velocities. AIMD simulations of a water molecule colliding with NO+.(H2O)4 to form NO+.(H2O)5 were performed to establish whether the resulting activated complex, with excess energy, would be more susceptible to forming a protonated water cluster and nitrous acid. The simulations showed that an intramolecular reaction could occur and was dependant on the impact direction and velocity of the incoming water molecule.